Determining the Success of Carbon Capture and Storage Projects - Dominique Thronicker; Ian A. Lange (Center for Economic Studies and ifo Institute (CESifo), 2015)
Carbon Capture and Storage (CCS) is regarded as one of the most important technologies to mitigate climate change while providing fossil-fuel based energy security. During the past decade, projects in support of the development and deployment of the technology have been initiated across the globe. However, a considerable number of these projects have later been put on hold or cancelled. Currently, there is little understanding of what characteristics may have led to these undesirable outcomes. Using data on planned, cancelled and operational CCS projects to date, this paper aims to elicit technological, economic and policy characteristics that render CCS projects more or less likely to become operational. The results consistently find that confirmation of storage site and capture processes that are pre-combustion, industrial separation, or natural gas separation increase the probability of project success, while presence of a carbon policy and non-commercial storage of CO2 are negatively linked to project success.
Keywords: L51; Q50; H30; 330; carbon capture and storage; regression analysis; carbon policy; technological change